Integrating Health Education in Core Curriculum Classrooms: Successes, Challenges, and Implications for Urban Middle Schools. (2nd November 2017) - Rajan, Sonali; Roberts, Katherine J.; Guerra, Laura; Pirsch, Moira; Morrell, Ernest
ABSTRACT: BACKGROUND: School‐based health education efforts can positively affect health behaviors and learning outcomes; however, there is limited available time during the school day for separate health education classes. The purpose of this study was to assess the feasibility and sustainability of implementing a classroom‐based health education program that integrates skill development with health learning. METHODS: A wait‐list control study design was conducted among 168 6th graders in 2 urban schools. Data on program implementation, feasibility, and health outcomes were collected from students at 3 time points and from 5 teachers across the implementation of the 10‐week program. RESULTS: There were barriers to implementation, including time limitations, unexpected school‐wide disruptions, and variations in student reading ability and teacher preparedness. However, analyses revealed there were significant increases in self‐efficacy regarding fruit and vegetable consumption and outcome expectations following program implementation, which were also sustained post‐program implementation. Despite inconsistent implementation in the wait‐list control school, small gains were also noted following the completion of the program. CONCLUSIONS: Integrating health education efforts within core curricula classes can lead to favorable outcomes. However, implementation barriers must be actively addressed by schools and program developers to improve program fidelity and maximize the sustainability of program gains.